2013
DOI: 10.7771/2159-6670.1071
|View full text |Cite
|
Sign up to set email alerts
|

The 2012 Pilot Source Study (Phase III): Response to the Pilot Certification and Qualification Requirements for Air Carrier Operations

Abstract: The 2012 Pilot Source Study (Phase III) was a continuation of the 2010 Pilot Source Study (Smith, Bjerke, NewMyer, Niemczyk & Hamilton, 2010), using the same research design with a new data set containing no duplicate records. University faculty and students assisted seven regional airlines to enter data on 4,024 pilots hired between 2005 and 2011. New-hire pilots' college and piloting backgrounds defined their input (Source) variables. Training and first year operations data defined the output (Success) varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…The first ''Pilot Source Study 2010'' (Smith et al, 2010) found that ''[s]tatistically, the best performing pilots were those who had flight instructor certificates, graduated from collegiate accredited flight programs, received advanced (post-private) pilot training in college, graduated with collegiate aviation degrees (any aviation discipline), and had between 500 and 1,000 preemployment flight hours'' (p. 73). The second ''Pilot Source Study 2012'' (Smith et al, 2013) continued the work from Smith and colleagues (2010) with a different dataset and reached similar conclusions.…”
Section: Review Of the Literaturementioning
confidence: 52%
See 2 more Smart Citations
“…The first ''Pilot Source Study 2010'' (Smith et al, 2010) found that ''[s]tatistically, the best performing pilots were those who had flight instructor certificates, graduated from collegiate accredited flight programs, received advanced (post-private) pilot training in college, graduated with collegiate aviation degrees (any aviation discipline), and had between 500 and 1,000 preemployment flight hours'' (p. 73). The second ''Pilot Source Study 2012'' (Smith et al, 2013) continued the work from Smith and colleagues (2010) with a different dataset and reached similar conclusions.…”
Section: Review Of the Literaturementioning
confidence: 52%
“…The Pilot Source Study 2015 demonstrates that the most successful regional airline candidate is one who advanced to a regional airline within four years after graduation; had an R-ATP with fewer than Since existing data do not directly measure safety; it is inferred in this study that pilot performance is linked to safety. In the Pre-Law Pilot Source Studies 2010 and 2012, many pilots earned Commercial Pilot certificates and were hired by regional airlines with fewer than 1,500 total flight hours; these pilots out-performed their classmates in terms of completions and extra training events (Smith et al, 2010;Smith et al, 2013). The Post-Law Pilot Source Study 2015 in essence studied the effects of the gap that was extended by PL 111-216.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2012 Pilot Source Study (Smith et al, 2013) was commissioned to retrieve data from seven additional regional airlines. Focusing on the variables collected in the first study, the 2012 Pilot Source Study analyzed 4,024 new pilot records and found that pilot background characteristics were very similar to pilots in the 2010 Pilot Source Study.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…AABI is an organization of aviation stakeholders (e.g., educators, practitioners, industry representatives, airlines, and manufacturers) that evaluates the quality of collegiate aviation programs seeking accreditation. In order to provide critical data to the ARC, AABI initiated research studies that became known as the Pilot Source Study of 2010 (Smith, Bjerke, NewMyer, Niemczyk, & Hamilton, 2010) and the Pilot Source Study of 2012 (Smith et al, 2013). Information from those studies was important in providing factual data related to the potential effects of the Pilot Certification and Qualification Requirements for Air Carrier Operations Rule (FAA, 2012), hereafter referred to as the FOQ Rule.…”
Section: Introductionmentioning
confidence: 99%